Inflammatory myofibroblastic tumor in a patient with X-Linked hypophosphatemia: A case of Occam's razor or Hickam's dictum? - Farhan Chowdry; Kelsey M. Miller; Ersan Altun; Sara E. Wobker; Gary S. Gottesman; Hikmat Al-Ahmadie; Tracy L. Rose; Eric M. Wallen; Matthew I. Milowsky (Urology Case Reports, 2024)
We present the case of a patient with X-Linked Hypophosphatemia (XLH) and an inflammatory myofibroblastic tumor (IMT) of the bladder which prompted further investigation into the possible relationship between XLH and IMT i.e. a case of Occam's Razor or Hickam's Dictum?